Unveiling TikTok's Impact on Youth Communication: Mengungkap Dampak TikTok pada Komunikasi Anak Muda - Sabila, Amelia Hidayatus; Hadi, Bintang Khalishah; Gimnastiar, Ahmad; Abadi , Totok Wahyu (Universitas Muhammadiyah Sidoarjo, 2024)
This study aims to investigate the impact of TikTok as a web-based entertainment platform on young people's communication development. The research uses a bibliometric analysis approach, drawing from scientific articles and journals indexed by Crossref and sourced via Google Scholar, covering the years 2013-2023. Data collection involved using the Publish or Perish (PoP) program to gather bibliographic information, which was then validated and manually inputted using Mendeley Desktop. Analysis was performed with VOSviewer to create mapping visualizations. Results showed the highest Crossref publication index in 2020 with 96 publications. Keyword analysis identified five clusters, with Cluster 1 containing 102 items in red. The term